Analisis Hasil Tes Sprint 30 Meter Dan Bleep Test Atlet Putri Ku 14 Club Basket CLS Surabaya - Wicaksono, Gigih Tri; Kusuma, Donny Ardi (Journal of Sport Science and Education, 2021)
In this study, the aim of this research is to find out how the description of the physical ability of the aerobic endurance and speed of the CLS Surabaya basketball club. This type of research is descriptive quantitative. The population in this study were female athletes of the age group 14 CLS Surabaya and the total sample was 18 athletes. The independent variables in this study are speed and endurance and the dependent variable in this study is the analysis of the test. It shows that the 30 meter running speed running speed test is in the moderate category with an average of 5.2 seconds, while aerobic endurance (VO2max) using the bleep test is in a very good category with an averange of 43.80 O2/kgBW/minute. The analysis of the results of the 30 meter running test and bleep test can be concluded that the speed test of the CLS Surabaya female athlete in the moderate category obtained an average value is 5,90 while the endurance test got the athletes ability test in the very good category of 43,80. It can be concluded that the speed of cls KU 14 female athletes belongs to the category lessonce while endurance belongs to the category very well.